Pemanfaatan Linkedin Sebagai Digital Marketing PT Vfirst Komunikasi Indonesia Dalam Membangun Brand Awareness di Indonesia - Dewi Pratiwi (KALBISCIENTIA Jurnal Sains dan Teknologi, 2022)
The digital era, provides opportunities for B2B companies to market their products through social media. Social media is one of the digital marketing strategies that are most chosen by business people because it is effective enough to connect with customers so that it can create brand awareness, generate leads, audience conversions, and more. This is the goal of PT. VFirst Communications Indonesia or commonly called VFirst, to implement digital marketing strategies. However, VFirst does not yet have a strong marketing team in doing digital marketing because all marketing activities are still being taken over and regulated by the central marketing team in India. VFirst in Indonesia entrusts Lead Generation to carry out digital marketing strategies by using LinkedIn to build brand awareness. This study was conducted to determine the use of LinkedIn as VFirst digital marketing in building brand awareness. The research method used is qualitative with in-depth interview data collection techniques. The results showed that the implementation of digital marketing through LinkedIn in building brand awareness in accordance with the main concepts used, with the selection of appropriate channels and interesting content as well as an approach to prospective customers carried out by the Lead Generation division succeeded in creating brand awareness from VFirst at the stage of recognition as a digital communication solution company.